«Un’interminabile luciferino Settecento». Il meridiano critico di Roberto Rovers - Ritrovato, Salvatore (L'ospite ingrato, 2024)
This article explores the reasons and the methods with which Roberto Roversi edits his anthology of Arcadian poetry from early 1700s to Parini. For Roversi this book represents an important moment to develop his critical view of the Eighteenth century, dealt without bias and in all its complexity. He identifies the details, nuances and the secondary paths of every author.